Sol-gel synthesis of organic-inorganic polymer electrolytes as membranes for fuel cells - Diedericks, Engela Elizabeth (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.) -- University of Stellenbosch, 1999.